PD-like FLC with Admittance Control of Hexapod Robot’s Leg Vertical Positioning for Seabed Locomotion - Addie Irawan, Hashim; Alam, Md. Moktadir (2015)
This paper presents a proposed Proportional and Derivative (PD)-like Fuzzy Logic Control (FLC) (PD-FLC) on dynamic control for vertical positioning of Hexapod Robot walking on seabed environment. The study has been carried out by modeling the buoyancy force following the restoration force to achieve the drowning level according to the Archimedes’ principle. The restoration force need to be positive in order to ensure robot locomotion is not affected by buoyancy factor. As for this force control solution, PD-FLC is used and integrated with admittance control that based on the total of force of foot placement by considering Center of Mass (CoM) of the robot during walking period. This integrated control technique is design and verify on the real-time based 4 degree of freedom (DoF) leg configuration of hexapod robot model. The scope of analysis is focus on walking on the varied stiffness of undersea bottom soil with tripod walking pattern. Moreover the verification is done on the vertical foot motion of the leg and the body mass coordination movement during walking period. The results shows that proposed PD-FLC admittance control able to cater the force restoration factor by making vertical force on each foot bigger enough (sufficient foot placement) if compare to the buoyancy force of the ocean, thus performing stable tripod walking on the seabed with uncertain stiffness.